Efektivitas Penggunaan Lembar Balik sebagai Media Promosi Kesehatan : Tinjauan Sistematis - Sutrisno Sutrisno; Rendi Ariyanto Sinanto (Jurnal Kesehatan Terpadu (Integrated Health Journal), 2022)
Good health promotion media can support health promotion efforts. The selection of health promotion media must be by the existing problems. Handling nutrition and stunting problems requires health promotion media to combine the problem's complexity with primary, secondary, and tertiary targets. The flipchart form is a suitable health promotion medium for nutritional and stunting problems. This study aims to measure and show evidence as a health promotion media. The research method is a systematic review using Garuda The Ministry of Education, Culture, Research, and Technology journal data sources. Data can be downloaded from March 10-17, 2021. Thirty-two articles matched the specified keywords. Ten papers were reviewed after being selected and determined according to the inclusion criteria. The results showed the health promotion media in the form of adequate sheets for learning nutrition and stunting education for the community. The influence of using sheets as a media for health promotion on changes in the community's knowledge, attitudes, and behavior about nutrition or other health problems.